IMPACT OF ACTIVE VIDEO GAMES ON SEDENTARY BEHAVIORS IN SCHOOL-AGE CHILDREN - DÁVILA-MORÁN, ROBERTO CARLOS (2024)
IN THE CONTEMPORARY LANDSCAPE, VIDEO GAMES HAVE EVOLVED FROM SIMPLE PASTIMES TO INTERACTIVE AND IMMERSIVE FORMS OF ENTERTAINMENT THAT SPAN A WIDE RANGE OF GENRES AND PLATFORMS. HOWEVER, THIS DEVELOPMENT HAS ALSO RAISED CONCERNS ABOUT THE INCREASE IN SEDENTARY BEHAVIORS AMONG SCHOOL-AGE CHILDREN, WHICH COULD CONTRIBUTE TO HEALTH PROBLEMS SUCH AS CHILDHOOD OBESITY AND OTHER LIFESTYLE DISEASES. THE OBJECTIVE OF THIS STUDY WAS TO ESTABLISH THE IMPACT OF ACTIVE VIDEO GAMES ON SEDENTARY BEHAVIORS IN SCHOOL-AGE CHILDREN FROM A PERUVIAN EDUCATIONAL INSTITUTION. THE STUDY HAS A QUANTITATIVE APPROACH AND A NON-EXPERIMENTAL DESIGN, APPLIED AND EXPLANATORY LEVEL, WAS ADOPTED. THE SAMPLE WAS SELECTED THROUGH INTENTIONAL NON-PROBABILISTIC SAMPLING, COMPOSED OF 121 SECOND, THIRD AND FOURTH GRADE STUDENTS FROM A PERUVIAN EDUCATIONAL INSTITUTION AND THEIR PARENTS. THE QUESTIONNAIRE WAS USED TO COLLECT THE DATA. THE RESULTS INDICATE THAT THE USE OF ACTIVE VIDEO GAMES REACHED 39.67% (48) OF THE PARTICIPANTS PRESENTED A MEDIUM LEVEL. REGARDING THE SEDENTARY BEHAVIOR VARIABLE, IT WAS FOUND THAT 45.45% (55) OF THE PARTICIPANTS PRESENTED A LOW LEVEL. IT IS CONCLUDED THAT WHEN EXAMINING THE LINEAR REGRESSION COEFFICIENT R, WHICH STANDS AT 0.274, IT IS FOUND THAT ACTIVE VIDEO GAMES HAVE AN IMPACT OF 27.4% ON SEDENTARY BEHAVIORS. © COPYRIGHT: FEDERACIÓN ESPAÑOLA DE ASOCIACIONES DE DOCENTES DE EDUCACIÓN FÍSICA (FEADEF)